Multistakeholder platforms for linking small farmers to value chains: Evidence from the Andes - Thiele, Graham; Devaux, André; Reinoso, Iván; Pico, Hérnan; Montesdeoca, Fabián; Pumisacho, Manuel; Andrade-Piedra, Jorge; Velasco, Claudio; Flores, Paola; Esprella, Raúl; Thomann, Alice; Manrique, Kurt; et al. (International Food Policy Research Institute, 2016)
Analyses of work in the Andes (Chapter 8; Cavatassi et al. 2011) indicate that platforms that bring stakeholders together around value chains can result in new products, processes, norms, and behaviors that benefit poor farmers in ways that would not have been achieved otherwise.